2022
DOI: 10.1111/odi.14264
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sjögren's syndrome in patients with dry mouth in the region of Central Hungary

Abstract: ObjectiveOne‐third of the Hungarian population suffers from xerostomia. Since there is no evidence of the actual prevalence of Sjögren's syndrome (SS) in Hungary, this study aimed to evaluate the same.Materials and MethodsData were collected from the Faculty of Dentistry, Semmelweis University from 2008 to 2015. A diagnosis of SS was established based on the American College of Rheumatology and European League Against Rheumatism criteria.ResultsOf the 1076 patients examined with sicca symptoms, 188 patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Based on a large scale, prospective cohort study (1726 labial gland biopsies), however, the clinical/lab findings may not always correlate with the morphological alterations [ 22 ]. Similar data have also been provided by a Hungarian study [ 4 ], where a positive focus score was only found in 109 cases (31.8%) out of 342 biopsies from patients with Sicca symptoms.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Based on a large scale, prospective cohort study (1726 labial gland biopsies), however, the clinical/lab findings may not always correlate with the morphological alterations [ 22 ]. Similar data have also been provided by a Hungarian study [ 4 ], where a positive focus score was only found in 109 cases (31.8%) out of 342 biopsies from patients with Sicca symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…Although its frequency may vary considerably depending on the classification criteria used, on the clinical or pathological settings, or on the age groups studied, the estimated prevalence of the primary forms in a US population-based cohort was reported as 22/100,000 inhabitants [ 2 ], but this figure in Europe is around 39/100,000 [ 3 ]. A recent report in Hungary claimed a lower incidence (16/100,000) of newly diagnosed SS cases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…SS patients often present first to their oral health professional because of their predominantly oral symptomatology, mainly xerostomia. 4 , 5 Hence, stomatologists are frequently the first practitioners to detect the signs of SS, and then rheumatologists are usually the practitioners to manage the systemic symptomatology, such as fatigue, lymphoma, interstitial lung disease, arthralgia, and Raynaud phenomenon, in the middle and late stages of the disease. 6 , 7 , 8 Given the complex and numerous challenges of diagnosing and treating this syndrome, increasingly large number of papers regarding SS have been published.…”
Section: Introductionmentioning
confidence: 99%